Homeric Stitchings: The Homeric Centos of the Empress Eudocia - Usher, M. D. (Rowman & Littlefield Publishers, 1998)
Homeric Stitchings is the first extended study of the Homeric Centos, a long pastiche poem on a biblical theme composed by the Theodosian Empress Eudocia using only verses from the Iliad and the Odyssey. Building upon recent work on Homeric poetics, and utilizing linguistic and semiotic methods of analysis, this study introduces readers to the Centos as a sophisticated comparative reading of Homer and the Bible, based upon intertextual associations of ideas, words, and sounds. Homeric Stitchings is a study in the performative aspects of ancient reading, the processes of human memory, and the reception of Homeric poetry as oral poetry in later antiquity. It will be of great interest to students and scholars of Homer, the Bible and comparative literature, and cultural historians.